Failure mechanism of the large‐section roadway under mined zones in the ultra‐thick coal seam and its control technology. Issue 4 (2nd December 2019) - Tai, Yang; Xia, Hongchun; Meng, Xiangbin; Kuang, Tiejun
Abstract: Aiming at serious deformation and failure of large‐section coal roadway under mined zones in ultra‐thick coal seam, its deformation and failure characteristics are analyzed based on the field measurement. This paper reveals the mechanism of roadway roof separation, roof leakage, and right rib extrusion. Based on the mechanism, two kinds of secondary support schemes are proposed, that is, "grouting + I‐steel support + bolt" (scheme I) and "grouting + U steel support + anchor + anchor cable" (scheme II). The industrial experiment is carried out at 1070 auxiliary transportation roadway in Tashan Coal Mine. The measured results show that the roadway roof separations of the secondary support scheme I and II are only 1/11 and 1/46 of the original support scheme, respectively, while the lateral displacements of the roadway are only 1/7 and 1/44 of the original support scheme. It could be seen that the deformation and failure of the roadway surrounding rock have been well controlled. Abstract : This paper reveals the mechanism of roof bedding separation, roof leakage, and right rib extrusion. Based on the mechanism, two kinds of secondary support schemes are proposed.